Wieczór Pieśni - Gdański Chór Męski "Moniuszko". (Gdańsk : [s.n., 1927)
Program koncertu.
Keywords: Życie muzyczne -- Polska -- Gdańsk -- 1900-1945.; Gdańsk (Polska) -- 1920-1939 (Wolne Miasto) -- druki ulotne